PENGETAHUAN, SIKAP, DAN DUKUNGAN KELUARGA DENGAN UPAYA PENCEGAHAN KECACATAN PADA PENDERITA KUSTA - Salahuddin Liputo; Dewi Modjo (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Lepers is a chronic disease that caused by infection of mycrobacterium leprae, the first attacked peripheral nevers, and next attacked are skin, mucosa of the mouth, upper respiratory tract, system of retikuloindetial, eyes, muscle, bones, and testicular, except the system of central nervous. The purpose of this study is to know the relationship of knowledge, attitude, and family support in preventing effort of physical defect. The sample of this research are consist of 27 people, techniques sample in this study is total sampling. From the statistical test of chi-square found that there is a significant correlation between knowledge, attitude, and family support in preventing effort of physical defect.